Cost Effectiveness In Oral Health Education - Rahmi, Annafsa Zaky; Palupi, Dyah Nawang; Bramantoro, Taufan (International Journal of Psychosocial Rehabilitation, 2020)
For the several last decades, cost of oral health care service is spiralling high, especially in developing countries where the prevalence of oral disease is still high. Meanwhile, the oral disease especially dental caries is closely related to socioeconomic status, which people with lower financial status also have lower oral health status. However, lower oral health status can result in losing productivity. This study is aimed to know the cost effectiveness of oral health education. The oral health education and prevention programs are introduced to help improve the oral health status and, in the same time, lower the cost needed for dental services. The methods used for oral health education are vast in variety and should be designated according to participants’ oral health status. It can be concluded from collected studies that oral health education is effective for improving the oral health knowledge and practices of dental hygiene, while at the same time keep the cost low to help people have a better quality of life.